Morphological and mechanical evolution of nanostructured ZrN thin films under 165 keV argon ions irradiation. (January 2022) - Naceri, S.E.; Izerrouken, M.; Ghamnia, M.; Saoula, N.; Haid, F.; Sari, A.
Abstract: Zirconium nitride is a promising candidate ceramic material to be adopted as an inert matrix for transuranic fuel, a new fuel concept having as targets the closing of the nuclear fuel cycle, and reduce the environmental impact of nuclear waste. Nevertheless, the comprehension of radiation tolerance of zirconium nitride still limited. In this paper, we have studied the radiation stability of nanostructured zirconium nitride (ZrN) thin films using 165 keV argon-ions (Ar 2+ ) irradiation at room temperature. After irradiation, the microstructural, morphological and mechanical properties of the irradiated ZrN films were investigated and compared to an un-irradiated reference film. The grazing incidence X-ray diffraction tests (GI-XRD) revealed a (100) ZrN textured films, the atomic force microscope (AFM) and the scanning electron microscope (SEM) images showed that the as-deposited ZrN films were nano-crystalline with spherical grains of about 50 nm in size and rms surface roughness of about 1.175 nm. After irradiation, the estimate grains size was found to increase to 72 and 86 nm for films irradiated to 2.3 and 22.3 (dpa) respectively, indicating grains coalescence. The nano-hardness of the irradiated films compared to the un-irradiated film was decreased for both doses, while the XRD patterns demonstrate a crystalline ZrN even at the higher dose of 22.3 (dpa), suggesting along with AFM and SEM results grain growth without amorphisation. Highlights: Argon ions irradiation was adopted to emulate the fission gases radiation damages. The surface and grains morphology of ZrN was strongly altered after irradiation. Nanostructured ZrN showed promising resistance to radiation-induced amorphisation. The mechanical behaviour of ZrN was closely related to its surface morphology.